The Role of Female Principles as Leaders in the 21st Century Learning Organization - Sugiharti, Tanti (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
Discussion about female leadership is not to be separated from the issue of partnership and social justice role between men and women and this has been constructed by religion, customs and culture. Commonly, the literature on women and leadership is identified with bias, contradiction and paradox. Thus, masculine dominance is still visible for the classification of leadership and management dynamics.  In the last few decades we have seen various education institutions are racing to improve the quality of schooling. The role of school principals is quite significant in realizing the success of the learning process. One of the most important things the school leaders should do is to build a strong communication and collaboration with their staff which contributes directly to the learning process. And this is the significant strength of the female leaders.  While, in a learning organization, learning itself becomes a source of intrinsic satisfaction of its members and every individual in it has the fundamental desire to be part of the meaningful process. Hence, principals do have important roles in directing and guiding their schools to be effective learning organization. This descriptive study shows how female principals effectively lead their schools as strong learning organizations.